2018
DOI: 10.2140/agt.2018.18.3363
|View full text |Cite
|
Sign up to set email alerts
|

The universal quantum invariant and colored ideal triangulations

Abstract: The Drinfeld double of a finite dimensional Hopf algebra is a quasitriangular Hopf algebra with the canonical element as the universal R-matrix, and one can obtain a ribbon Hopf algebra by adding the ribbon element. The universal quantum invariant of framed links is constructed using a ribbon Hopf algebra. In that construction, a copy of the universal R-matrix is attached to each crossing, and invariance under the Reidemeister III move is shown by the quantum Yang-Baxter equation of the universal R-matrix. On … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 30 publications
0
4
0
Order By: Relevance
“…In the case of Uq(sl2), such identification of the factorization of the R-matrix appears in quantum Teichmüller theory [30] as an element of the mapping class group, and the corresponding factorization is also used to re-derive Kashaev's knot invariant [16]. This has been utilized for example to construct new quantum invariant for "colored triangulations" of topological spaces recently [40]. Although the two factorizations are realized on different tensor spaces, we believe there is a strong connection between the two different factorizations, where A is identified with the Borel part of Uq(g), and it will be interesting to find an explicit relationship between them.…”
Section: Universal R-matrix As Half-dehn Twistmentioning
confidence: 99%
“…In the case of Uq(sl2), such identification of the factorization of the R-matrix appears in quantum Teichmüller theory [30] as an element of the mapping class group, and the corresponding factorization is also used to re-derive Kashaev's knot invariant [16]. This has been utilized for example to construct new quantum invariant for "colored triangulations" of topological spaces recently [40]. Although the two factorizations are realized on different tensor spaces, we believe there is a strong connection between the two different factorizations, where A is identified with the Borel part of Uq(g), and it will be interesting to find an explicit relationship between them.…”
Section: Universal R-matrix As Half-dehn Twistmentioning
confidence: 99%
“…3 In [3], it was shown that the Wheeler-DeWitt equation for three-dimensional general relativity reduces to the pentagon relation. There is a comprehensive literature around the idea of representing Pachner moves of a triangulation in three dimensions by a solution of the pentagon equation (or a pentagon relation), see in particular [2,8,24,34,47,59]. In four dimensions, the dual hexagon equation plays a corresponding role [29] (also see Remark 6.2 below), in five dimensions it is the dual heptagon equation [35,36,37].…”
Section: Introductionmentioning
confidence: 99%
“…In the last two decades the universal invariant has been extensively studied [Hab08,Suz10,Suz13,MS16,Suz18]. Although the definition looks harmless, computing this invariant may turn out to be a challenging task.…”
Section: Introductionmentioning
confidence: 99%